The experience of bullying among adolescents receiving mental health care: an interpretative phenomenological analysis - Marjorie Roques; Solène Spiers; Mayssa' El Husseini; Didier Drieu; Dimitra Laimou; Nathalie de Kernier; Anne-Valérie Mazoyer; Fabian Guénolé (BMC, 2022)
Abstract Background Bullying, the most prevalent form of abuse among adolescents, is associated with emotional and behavioural problems as well as psychiatric morbidity. Moreover, it has been shown that adolescents with previous mental health problems are at increased risk of being bullied and that the psychopathological repercussions of bullying are greatest among them. However, little is known about the experience of bullying in adolescents receiving treatment from mental health services. The aim of this study was to explore the subjective experience of bullying in adolescents receiving mental health care. Methods The study was developed in the context of a French multicentre research program and employed an exploratory phenomenological approach. A purposeful sampling strategy was used to select adolescents who had experienced bullying (according to the Olweus criteria) and who were able to relate their experiences clearly. In-depth, semistructured interviews with participants were conducted; written transcriptions of these interviews were analysed using thematic analysis. Results Twenty-one adolescents (age range: 12-17 years; 13 girls) participated in the study. The analysis indicated a three-axis structure: (1) negative emotions and violent feelings, describing adolescents' fear, sadness, aggression against themselves, and generalized mistrust; (2) isolation and loneliness, underlining the need to take refuge within oneself and the experiences of rejection, helplessness, and secret-keeping; and (3) self and identity repercussions, including experiences of shame and lowered self-esteem, identity questions, and a vision of bullying as a life experience. Conclusions The results of this study may have practical implications for clinicians: (1) a situation of bullying should be sought when an adolescent is seen for unexplained externalized behavioural misconduct; (2) low levels of emotional expression in a bullied adolescent may warn about associated self-harm; (3) a bullied adolescent's tendency to hide this situation from his or her parents may reflect underlying family-related vulnerability; and (4) the phenomenological analysis showed potential particularities in the assumptive world of these adolescents and suggested that relationality may play a crucial role in their experiences. These results suggest incentives to design specific individual and group therapeutic interventions for bullied adolescents with significant levels of social withdrawal, including family support. Additional research is necessary to improve our understanding of the psychopathological and intersubjective aspects of bullying in adolescents.